Ultra-large chemical libraries for the discovery of high-affinity peptide binders - Anthony J. Quartararo (Nature Portfolio, 2020)
Synthetic peptide libraries can access broad chemical space, but generally examine only ~ 106 compounds. Here, the authors show that in-solution affinity selection, interfaced with nLC-MS/MS sequencing, can identify binders from fully randomized synthetic libraries of 108 members.